MDMA-assisted therapy for posttraumatic stress disorder: A pooled analysis of ethnoracial differences in efficacy and safety from two Phase 2 open-label lead-in trials and a Phase 3 randomized, blinded placebo-controlled trial. (August 2022) - Ching, Terence HW; Williams, Monnica T; Wang, Julie B; Jerome, Lisa; Yazar-Klosinski, Berra; Emerson, Amy; Doblin, Rick
Background: Limited ethnoracial diversity in previous ±3, 4-methylenedioxymethamphetamine-assisted therapy (MDMA-AT) trials for posttraumatic stress disorder (PTSD) has prompted questions concerning whether Black, Indigenous, and People of Color (BIPOC) also benefit from this treatment. Methods: Secondary analysis was conducted using a modified intent-to-treat sample pooled from two Phase 2 open-label trials and a Phase 3 randomized, blinded placebo-controlled trial to compare efficacy and safety of MDMA-AT for PTSD between BIPOC and non-Hispanic White participants. Four subgroups were of interest: MDMA-AT, BIPOC ( n  = 20); MDMA-AT, non-Hispanic White ( n  = 63); Placebo-assisted therapy (Placebo-AT), BIPOC ( n  = 17); and Placebo-AT, non-Hispanic White ( n  = 27). Planned comparisons tested subgroup differences in changes in Clinician-Administered PTSD Scale for DSM-5 (CAPS-5) scores from baseline to primary endpoint, controlling for study type and baseline scores. Adverse events (AEs) on the day of (day 0) to 2 days post-dosing were reported for each subgroup. Results: In the MDMA-AT group, no significant ethnoracial difference in CAPS-5 change scores was observed. In the Placebo-AT group, BIPOC participants trended toward greater reductions in CAPS-5 scores than non-Hispanic Whites. Among non-Hispanic Whites, MDMA-AT was accompanied by significantly greater reductions in CAPS-5 scores than Placebo-AT. No treatment difference emerged among BIPOC participants. AEs were mostly rated as mild or moderate across subgroups. Conclusions: These findings provide preliminary support for the efficacy and safety of MDMA-AT for treating PTSD across ethnoracial groups. There was also a trend toward greater efficacy with Placebo-AT among BIPOC participants. There was an imbalance in subgroups, highlighting the need for culturally responsive recruitment strategies to diversify future studies.